Priority issues of public health of student youth in a higher school - Karabalayeva, A.B.; Ibadullayeva, S.Zh.; Abilbek, Zh.; Abilova, Sh.B. (KU Publ., 2021)
Improving health in an educational environment allows to gain greater control over the health of students. It includes a wide range of educational and methodological activities aimed at protecting and improving the health of subjects of the educational process and improving their quality of life through the correct organization of the educational environment, and not only prevention and correction. This policy should be supported by an appropriate regulatory framework that combines the stimulation of experience and knowledge based on high-quality evidence-based information, verified health evidence, develops intellectual assets and applies ethical standards in the practice of maintaining the health of students at the university. Partnerships between public health services of the Republic of Kazakhstan and higher educational institutions are obliged to identify and share responsibility for the health of the student community and solve problems that contribute to the development of key tasks in the field of protection and preservation of public health, requiring additional efforts and mobilization of resources of the higher education system. At the republican level the functions of monitoring public health risk factors in the conditions of training students in higher education are carried out. Scientific research in the field of public health, including measures to promote healthy lifestyles, makes it possible to predict their dynamics and assess the effectiveness and quality of educational services and implementation programs for the preservation of public health. The activities of higher educational institutions in the Republic of Kazakhstan are considered from the point of view of health as the main value. A healthy student community and its well-being are based on the consolidation of efforts and available methods of preserving and developing the health of future professionals.
Жоғары мектеп жағдайындағы студент жастардың қоғамдық денсаулығының басты мəселелері
Приоритетные вопросы общественного здоровья студенческой молодежи в условиях высшей школы
Keywords: educational environment; health promotion; targeted programs; educational environment; stroboscopic effect; psychological visual defect; professionalization; visualization